2008
DOI: 10.1055/s-2008-1046731
|View full text |Cite
|
Sign up to set email alerts
|

Periphere arterielle Verschlusskrankheit: Prädiktoren und Behandlungsintensität

Abstract: The INVADE project confirms the high prevalence of PAD in an elderly population. These data underline the importance of measuring hsCRP for diagnosing and following PAD development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This high prevalence of asymptomatic PAD in our population is comparable to the prevalence reported in other Arab and non-Arab populations, such as the cohorts in Germany, Switzerland, France, Japan, and Turkey. [ 21 24 ] Likewise, in the Arabian Gulf, Kownator et al reported a prevalence of asymptomatic PAD of 13.7% in patients with a single previous coronary or cerebrovascular event, with the highest reported in Kuwait (16.3%) and the United Arab Emirates (14.7%), and the lowest in Qatar (5.3%). [ 23 ] In the present study, we found that old age, hypertension, diabetes mellitus, hyperlipidemia, current smoking, previous CABG, and history of stroke were the main predictors of PAD in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…This high prevalence of asymptomatic PAD in our population is comparable to the prevalence reported in other Arab and non-Arab populations, such as the cohorts in Germany, Switzerland, France, Japan, and Turkey. [ 21 24 ] Likewise, in the Arabian Gulf, Kownator et al reported a prevalence of asymptomatic PAD of 13.7% in patients with a single previous coronary or cerebrovascular event, with the highest reported in Kuwait (16.3%) and the United Arab Emirates (14.7%), and the lowest in Qatar (5.3%). [ 23 ] In the present study, we found that old age, hypertension, diabetes mellitus, hyperlipidemia, current smoking, previous CABG, and history of stroke were the main predictors of PAD in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The present review did not identify any other pharmacologic trials in screen-detected PAD populations reporting patient health outcomes. Observational studies suggest both functional and mortality benefits of statins . An RCT of statin therapy in individuals with an abnormal ABI may be of uncertain value because many of these individuals may qualify for statin therapy based on 10-year risk alone—data from a 2008 large, individual participant data meta-analysis suggest that 95% of men and 41% of women with an ABI of 0.9 or less would already be above a 10% Framingham Risk Score 10-year risk threshold …”
Section: Discussionmentioning
confidence: 99%